SENSITIVITY OF POTATO CULTIVARS TO FOMESAFEN AND METRIBUZIN - Golubev, Artem (Potato Journal, 2022)
The objective of this research was to evaluate the sensitivity of 3 potato cultivars (different ripening periods)to fomesafen (300 g/ha a.i.) and metribuzin (980 g/ha a.i.) herbicides applied preemergence (PRE). The experiments wereconducted during 2020 and 2021 in the Leningrad region of the Russian Federation. The application of herbicides at allthree potato cultivars caused slight yellowing of tips of the leaves (less than 5%). This symptom of phytotoxicity wasmore noticeable in the early season cultivars Udacha (ripening time from 65 days) and Nevsky (ripening time from 75days). The negative effect of herbicides on plant height was demonstrated in arid conditions (in 2021), when after applyingfomesafen and metribuzin there was a significant delay in plant growth in two cultivars (Udacha and Avrora) at 7 and14 days after emergence (DAE). By 28 DAE, the plant height of all three cultivars after herbicide treatments and in thenontreated check were equalized (differences did not exceed 10%). Despite the observed symptoms of phytotoxicity, noneof the herbicide treatments in both years didn’t show a statistically significant negative effect of herbicides on potatoyield, indicating the high regenerative capacity of potatoes.